An Analog Integrated Circuit Beamformer for High-Frequency Medical Ultrasound Imaging - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2012)
We designed and fabricated a dynamic receive beamformer integrated circuit (IC) in 0.35-mu m CMOS technology. This beamformer IC is suitable for integration with an annular array transducer for high-frequency (30-50 MHz) intravascular ultrasound (IVUS) imaging. The beamformer IC consists of receive preamplifiers, an analog dynamic delay-and-sum beamformer, and buffers for 8 receive channels. To form an analog dynamic delay line we designed an analog delay cell based on the current-mode first-order all-pass filter topology, as the basic building block. To increase the bandwidth of the delay cell, we explored an enhancement technique on the current mirrors. This technique improved the overall bandwidth of the delay line by a factor of 6. Each delay cell consumes 2.1-mW of power and is capable of generating a tunable time delay between 1.75 ns to 2.5 ns. We successfully integrated the fabricated beamformer IC with an 8-element annular array. Experimental test results demonstrated the desired buffering, preamplification and delaying capabilities of the beamformer.
Keywords: All-pass filter; analog delay; beam forming; biquad current mirror; delay line; ultrasound imaging; PRML READ/WRITE CHANNEL; MATRIX TRANSDUCER; CMUT ARRAYS; LOW-POWER; DESIGN; CHIP